USGS Benchmark Glacier Mass Balance and Project Data ... - Emily H Baker; Emily H Baker; Christopher J. Mcneil; Christopher J. Mcneil; Louis Sass; Louis Sass; Erich H Peitzsch; Erich H Peitzsch; Erin N Whorton; Erin N Whorton; Caitlyn E Florentine; Caitlyn E Florentine; et al. (U.S. Geological Survey, 2018)
This link has been superseded. The data are available at: https://doi.org/10.5066/P9AGXQSR ...